2020
DOI: 10.3390/antiox9080646
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Drug Potential of Tryptophan-Betaxanthin and Related Plant Betalains in the Caenorhabditis elegans Tumoral Model

Abstract: Betalains are plants pigments identified as potent antioxidant molecules, naturally present in foods like beetroot and prickly pears. Although activities described for betalain-containing formulations include cancer prevention and treatment, the use of extracts instead of purified pigments has avoided the investigation of the real chemopreventive and chemotherapeutic potential of these phytochemicals. Three betalain-rich extracts and six individual pure betalains were used in this work to characterize the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
2
13
0
1
Order By: Relevance
“…In C. elegans, betalains reduced tumor growth by modulating DAF-16, extending longevity, and conferring resistance to stress in a gld-1 null mutant model, an orthologous gene model to the human QKI (KH domain with RNA binding capacity). [39] In addition, betaxanthin and betacyanin demonstrated cytotoxic potential in vitro at 0.35 and 0.25 μg/mL, respectively. Nevertheless, only betaxanthin could induce apoptotic signaling, albeit both betalains reduced interleukin-8 (IL-8) production, which is involved in the inflammatory process in some types of cancer, such as colon cancer.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In C. elegans, betalains reduced tumor growth by modulating DAF-16, extending longevity, and conferring resistance to stress in a gld-1 null mutant model, an orthologous gene model to the human QKI (KH domain with RNA binding capacity). [39] In addition, betaxanthin and betacyanin demonstrated cytotoxic potential in vitro at 0.35 and 0.25 μg/mL, respectively. Nevertheless, only betaxanthin could induce apoptotic signaling, albeit both betalains reduced interleukin-8 (IL-8) production, which is involved in the inflammatory process in some types of cancer, such as colon cancer.…”
Section: Resultsmentioning
confidence: 93%
“…In C. elegans , betalains reduced tumor growth by modulating DAF‐16, extending longevity, and conferring resistance to stress in a gld‐1 null mutant model, an orthologous gene model to the human QKI (KH domain with RNA binding capacity) [39] . In addition, betaxanthin and betacyanin demonstrated cytotoxic potential in vitro at 0.35 and 0.25 μg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, among the betalains tested, tryptophan-Bx ( 23 ) showed the greatest effect on the size of the tumor by reducing its size by 56.4% in the animal model of Caenorhabditis elegans (cancer strain JK1466) and extended the animal’s lifespan by 9.3%, which indicates high effectiveness and low toxicity [ 63 ]. According to our results, tryptophan-Bx ( 23 ) showed strong activity against HeLa and RKO cell lines, so further in vitro and in vivo studies in this direction on the pure compound are also worth considering.…”
Section: Resultsmentioning
confidence: 99%
“…In the interesting tumor model of Caenorhabditis elegans strain JK1466, tumor growth was inhibited by betanin, indicaxanthin, tryptophan-betaxanthin and phenylethylamine-betaxanthin. Interestingly, the sequence of anti-tumor effectiveness of the betalains studied did not correspond to the sequence of their antioxidant effectiveness in vitro and in vivo [ 223 ]. The mechanism of the anticancer action of betalains is still not clear, but it has been demonstrated that betalains affect the expression of some genes related to cell growth and apoptosis [ 216 ].…”
Section: Health Benefitsmentioning
confidence: 99%